Macroprudential Liquidity Stress Testing in FSAPs for Systemically Important Financial Systems - Jobst, Andreas A. (IMF Working Papers; Working Paper ;, 2017)
Bank liquidity stress testing, which has become de rigueur following the costly lessons of the global financial crisis, remains underdeveloped compared to solvency stress testing. The ability to adequately identify, model and assess the impact of liquidity shocks, which are infrequent but can have a severe impact on affected banks and financial systems, is complicated not only by data limitations but also by interactions among multiple factors. This paper provides a conceptual overview of liquidity stress testing approaches for banks and discusses their implementation by IMF staff in the Financial Sector Assessment Program (FSAP) for countries with systemically important financial sectors over the last six years.